Security Data Aggregation with Recoverable Data in Heterogeneous Wireless Sensor Network - Lusheng Shi; Huibo Zhu; Lin Chen (Dianxin kexue)
Recently, many security aggregation algorithms in wireless sensor network have high communication overhead and the usage of aggregation functions is constrained. A secure data aggregation algorithm with recoverable data in heterogeneous wireless sensor network was proposed. The algorithm uses homomorphism encryption techniques based on elliptic curve to address data privacy protection, and uses an efficient aggregate signature scheme to ensure data integrity and authenticity. The unique data recovery function of this algorithm can recover individual data together with getting the aggregated results, and can facilitate the follow-up operation, and enrich the aggregate type. The algorithm takes full advantage of the difference of nodes in heterogeneous wireless sensor network, and diverts large number of calculation work to h-sensors, this approach improves the efficiency of the implementation. Simulation and comparative analysis show that algorithm has high safety and high efficiency, although the communication overhead of single aggregate process is high, data recovery process saves the overhead of the follow-up work, and the overall energy consumption is actually reduced.